Environmental pollutant induced cellular injury is reflected in exosomes from placental explants. (1st January 2020) - Sheller-Miller, Samantha; Radnaa, Enkhtuya; Arita, Yuko; Getahun, Darios; Jones, Richard J.; Peltier, Morgan R.; Menon, Ramkumar
Abstract: Introduction: Exosomes are intercellular signaling vesicles whose cargo reflects the physiological status of the cell of their origin and can regulate gene expression in other tissues. Polybrominated diphenyl ethers (PBDEs) and bisphenols (A [BPA], Tetrabromobisphenol A [TBBPA], and 2, 4, 6-Tribromophenol [TBP]) are common environmental pollutants known to increase the risk for spontaneous preterm birth (PTB). We hypothesized that placental exposure to these environmental pollutants causes exosome cargo changes that reflect exposure associated placental response. Methods: Full-term, C-section placenta explants were treated with PBDE congeners (47, 100, 153, 209), TBBPA, TBP or BPA for 24 h. Exosomes were isolated from media by sequential ultracentrifugation and purified by size exclusion chromatography. Exosomes were characterized by electron microscopy, nanoparticle tracking analysis and Western blot. Proteomics identified differentially expressed exosomal proteins and Ingenuity pathway analysis (IPA) determined biological functions and pathways represented by identified proteins. Results: Regardless of treatment, placental expressed exosomes markers (PLAP, CD9, CD63, 81 and ALIX), had a size distribution between 50 and 175 nm and were present in the conditioned medium at 5–8 x 10 11 exosomes/mL. Proteomic analysis identified 2598 proteins which demonstrated that specific pollutants caused differential expression of specific proteins, including alarmin, High Mobility Group Box 1 (HMGB1), MAPK14 (p38 MAPK) and GSK3β. IPA revealed an inhibition of pathways associated with cell survival, tissue repair and proliferation, as well as activation of cell death pathways (e.g. necrosis). Conclusion: Environmental exposure of placental explants did not change the quantity of exosomes or their characteristics. However, exosome cargo composition exposed to some environment pollutants may be involved in placental nuclear and cellular injury and inflammation. Highlights: Exosomes from environmental pollutants exposed placenta had classic features. Exosome characteristics were similar in pollutant exposed and control placenta. Exosomes carry differentially expressed protein cargo reflective of exposure. PBDEs and BPA/TBBP/246TBP produced exosome cargo reflective of placental injury.